Perplexing paradoxical reactions: navigating the complexity of protracted tuberculosis meningitis—a case report - Gooding, Megan S.; Hammoud, Dima A.; Epling, Brian; Rocco, Joseph; Laidlaw, Elizabeth; Kuriakose, Safia; Chaturvedi, Mansi; Galindo, Frances; Ma, Stella V.; Mystakelis, Harry; Poole, April; Russo, Kelly; et al. (Frontiers in Immunology, 2024)
Tuberculosis meningitis (TBM) has considerable mortality and morbidity, and it presents with therapeutic challenges including often being complicated by paradoxical reactions (PR). Here we describe the clinical course of four cases of TBM patients complicated by PR in a longitudinal TB cohort, while also providing insights from the larger clinical cohort. Research flow cytometry, biomarker analysis, and drug concentrations were performed on available samples.All participants were initiated on standard antituberculosis therapy (ATT) and enrolled at onset of PR (PR group) or 2-4 months after ATT start (controls). The four TBM participants highlighted here presented with fevers, headaches, neurological deficits, and fatigue at initial presentation. Upon diagnosis, all were initiated on RHZE at standard doses and corticosteroids.The median time to first PR was 37 days with recrudescence of initial TBM signs and symptoms at the time of PR. At the time of referral, all participants had low drug concentrations requiring dose optimization and regimen intensification as well as recrudescent flares upon corticosteroid taper, with one individual developing enlargement of tuberculoma one year following completion of ATT. Based on biomarkers and flow cytometry, PRs are characterized by elevated interferon gamma and ferritin levels in the plasma compared to controls. Within the TBM participants, T cell activation with elevated levels of inflammatory biomarkers in the CSF were seen at the time of PR. These unique and highly detailed TBM cases provide insights into the pathogenesis of PR that may assist with future diagnostics and treatment.